2019
DOI: 10.3847/2515-5172/ab09fa
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Chop Addition: Thermal IR Background Subtraction without Nodding

Abstract: Due to the large size and mass of the secondary mirror on next generation extremely large telescopes it will not be possible to provide classical chopping and nodding as is used during mid-IR observations today. As a solution to this we propose an alternative approach to thermal background reduction called 'inverse chop addition'. Here we use the symmetries of the thermal background to replace nodding, which allows us to get nearly identical background reductions while only using a special chopping pattern. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Recently, using test data on VLT/VISIR, we showed that a similar technique can achieve essentially the same signal/noise ratio as traditional chopping/nodding on the VLT. 7,16 Due to limitations in the VLT M2 mirror control, we could not test a three-point chopping method as Landau's, 15 but we could alternate on ≈ minute timescales between standard observations chopped North and observations chopped South. Combined, this "Inverse Chop Addition" resulted in a background subtraction that is on par with the standard chop/nod method, at least for short observations.…”
Section: Novel Background Removal Techniquesmentioning
confidence: 99%
“…Recently, using test data on VLT/VISIR, we showed that a similar technique can achieve essentially the same signal/noise ratio as traditional chopping/nodding on the VLT. 7,16 Due to limitations in the VLT M2 mirror control, we could not test a three-point chopping method as Landau's, 15 but we could alternate on ≈ minute timescales between standard observations chopped North and observations chopped South. Combined, this "Inverse Chop Addition" resulted in a background subtraction that is on par with the standard chop/nod method, at least for short observations.…”
Section: Novel Background Removal Techniquesmentioning
confidence: 99%
“…Once approximated as counts, a scaling factor of 1.85 is introduced to correct for the f/ratio difference between the raw imaging system using the supplied camera lens, and that via the optical system. Mid-IR background can be several orders of magnitude brighter than most astronomical sources (Pietrow et al 2019) and arises primarily from thermal emission from the sky, telescope and any structures visible to the detector (e.g.the optics and electronics). Temperature fluctuations in these components gives rise to noise and considerable background variability.…”
Section: Calibrationmentioning
confidence: 99%